1998
DOI: 10.1046/j.1365-8711.1998.01403.x
|View full text |Cite
|
Sign up to set email alerts
|

The Phoenix Deep Survey: 1.4-GHz source counts

Abstract: We present the first results from the Phoenix Deep Survey, a multiwavelength survey of a 2° diameter region. Observations in the radio continuum at 1.4 GHz carried out with the Australia Telescope Compact Array are described. The catalogue of over 1000 radio sources compiled from these observations is analysed, and the source counts are presented. We model the observational source counts using a two‐population model and published luminosity functions for these populations. Upon invoking luminosity and density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
173
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(184 citation statements)
references
References 5 publications
10
173
1
Order By: Relevance
“…In the southern hemisphere, the Australia Telescope Compact Array, (ATCA) has been used to study the Phoenix field (Hopkins et al 1998;, the Hubble Deep FieldYSouth ( Huynh et al 2005), and the Chandra Deep FieldYSouth and ELAIS SWIRE fields Afonso et al 2006). Combined VLA and MERLIN observations of the HDFN (Muxlow et al 2005) with a resolution of 0.2 00 show the complexity of the microjansky radio emission suggesting a mixture of AGNs and star formation which contributes to the submillijansky radio population.…”
Section: Radio Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the southern hemisphere, the Australia Telescope Compact Array, (ATCA) has been used to study the Phoenix field (Hopkins et al 1998;, the Hubble Deep FieldYSouth ( Huynh et al 2005), and the Chandra Deep FieldYSouth and ELAIS SWIRE fields Afonso et al 2006). Combined VLA and MERLIN observations of the HDFN (Muxlow et al 2005) with a resolution of 0.2 00 show the complexity of the microjansky radio emission suggesting a mixture of AGNs and star formation which contributes to the submillijansky radio population.…”
Section: Radio Studiesmentioning
confidence: 99%
“…References to other counts are PDFS and PDF ( Hopkins et al 1998), MC85 ( Mitchell & Condon 1985), OW84 (Oort & Windhorst 1985), ELIAS (Ciliegi et al 1999), HDF ( Richards 2000), and SSA13 ( Fomalont et al 2006). The highest flux density points are based on a compilation from Condon (1984).…”
Section: Source Countmentioning
confidence: 99%
“…The upturn in the source counts was initially explained through modelling of source populations with no need to include a substantial AGN contribution (e.g. Hopkins et al 1998). However, a growing number of studies are finding that lower luminosity AGN, both radio-loud and weakly radio emitting sources (radio-loud and radio-quiet AGN respectively), make a significant contribution to the sub-mJy population (Jarvis & Rawlings 2004;Huynh et al 2008;Seymour et al 2008;Smolčić et al 2008;Padovani et al 2009Padovani et al , 2011Bonzini et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The dominance of starburst galaxies in the sub-mJy population is already well established (Gruppioni et al 2008), where the number of blue galaxies with star-forming spectral signatures is seen to increase strongly. Rowan-Robinson et al (1993), Hopkins et al (1998), and others have concluded that the source counts at these faintest levels require two populations, AGNs and starburst galaxies. This latter population can best be modelled as a dusty star-forming population, under the assumption that they are the higher redshift analogues of the IRAS star-forming population (Rowan-Robinson et al 1993;Pearson & Rowan-Robinson 1996).…”
Section: Differential Countsmentioning
confidence: 98%
“…Note that Huynh et al (2005) used the radio luminosity function of Condon et al (2002) and derived a best fitting evolution parameterisation ∝(1 + z) 2.7 , slightly lower than the work presented here although the values are broadly consistent and differences can be due to the assumed SED and luminosity function. Hopkins (2004) and Hopkins et al (1998) used radio and infrared luminosity functions respectively obtaining evolution in the sub-mJy population ∝(1 + z) 2.7 and ∝(1 + z) 3.3 . It does however appear that the counts measured in this study lie at the lower end of the emerging picture on excess sub-mJy radio counts, as shown in Fig.…”
Section: Differential Countsmentioning
confidence: 99%